Quand le cinéma grec passe à table - Stéphane Sawas (Cahiers Balkaniques)
Pasta is not a typical Greek dish, but its presence on screen reveals the main tensions of Greek society. From The Adventures of Vilar (1924) to Xenia (2014) the characters eating pasta express, in relation with the political context, their desire for another life.